Criteria and influencing parameters for the design of piers of semi‐integral bridges. (4th September 2017) - Gebauer, Daniel; Stümpel, Marina; von der Haar, Christoph; Marx, Steffen
Abstract : This article deals with the challenges of semi‐integral construction of long viaducts. The main characteristic of semi‐integral bridges is the monolithic connection of most parts of the substructure with the superstructure. This leads to complex load‐bearing behavior, in which several structural components interact with each other. Because of the longitudinal movement of the superstructure, constraint forces and moments occur in the piers. They induce additional stresses in the structure compared to conventionally supported bridges. An important issue during the design process is the choice of the pier cross section. The stiffness and ductility of the piers influence the constraint moments and failure behavior of the pier. This is the reason why the detailed investigation into the influencing parameters (normal‐force utilization, reinforcement ratio, and width‐to‐height ratio) described in this paper was carried out. In this investigation, the moment–curvature relationship was used and the failure behavior as well as the constraint moments in the structure were evaluated.